Optimal Zcs Modulation for Bidirectionalhigh-Step-Ratio Modular Multilevel Dc-Dc Converter - Rojas-Lobos, F; Droguett-Olea, G (Institute of Electrical and Electronics Engineers Inc., 2021)
Recent developments in dc powered technologies have increased interest in highly efficient dc-dc converters, especially at high voltage and high-step voltage ratios. Modular multilevel converters (MMCs) are an attractive alternative approach to this demand because they can manage medium and high dc voltages while using standard semiconductor devices with high efficiency if they employ soft-switching techniques. However, the latest soft-switching techniques require resonant circuits, limiting their operation. This article proposes a new zero-current switching modulation technique for a high-step-ratio MMC dc-dc converter as result of a rms current minimization problem. The proposed optimization generates trapezoidal or triangular current to operate the converter over a wide output voltage and power range, while using a simple control scheme to regulate the output voltage and the voltage balance among the floating cell capacitors. The theoretical analysis has been verified with a laboratory-scaled prototype, demonstrating the effectiveness of the approach and excellent dynamical response. © 1986-2012 IEEE.